Efficient biosynthesis of d‐ribose using a novel co‐feeding strategy in Bacillus subtilis without acid formation. (6th December 2016) - Cheng, J.; Zhuang, W.; Li, N.N.; Tang, C.L.; Ying, H.J.
Abstract: Normally, lowd ‐ribose production was identified as responsible for plenty of acid formation by Bacillus subtilis due to its carbon overflow. An approach of co‐feeding glucose and sodium citrate is developed here and had been proved to be useful ind ‐ribose production. This strategy is critical because it affects the cell concentration, the productivity ofd ‐ribose and, especially, the formation of by‐products such as acetoin, lactate and acetate.d ‐ribose production was increased by 59·6% from 71·06 to 113·41 g l −1 without acid formation by co‐feeding 2·22 g l −1 h −1 glucose and 0·036 g l −1 h −1 sodium citrate to a 60 g l −1 glucose reaction system. Actually, the cell density was also enhanced from 11·51 to 13·84 g l −1 . These parameters revealed the importance of optimization and modelling of thed ‐ribose production process. Not only could zero acid formation was achieved over a wide range of co‐feeding rate by reducing glycolytic flux drastically but also the cell density andd ‐ribose yield were elevated by increasing the hexose monophosphate pathway flux. Significance and Impact of the Study: Bacillus subtilis usually produced ‐ribose accompanied by plenty of organic acids when glucose is used as a carbon source, which is considered to be a consequence of mismatched glycolytic and tricarboxylic acid cycle capacities. This is the first study to provide high‐efficiency biosynthesis ofd ‐ribose without organic acid formation in B. subtilis, which would be lower than the cost of separation and purification. The strain transketolase‐deficient B. subtilis CGMCC 3720 can be potentially applied to the production ofd ‐ribose in industry. Abstract : Significance and Impact of the Study: Bacillus subtilis usually produced ‐ribose accompanied by plenty of organic acids when glucose is used as a carbon source, which is considered to be a consequence of mismatched glycolytic and tricarboxylic acid cycle capacities. This is the first study to provide high‐efficiency biosynthesis ofd ‐ribose without organic acid formation in B. subtilis, which would be lower than the cost of separation and purification. The strain transketolase‐deficient B. subtilis CGMCC 3720 can be potentially applied to the production ofd ‐ribose in industry.